Supplement 1 - -, - (2014)
Some of the great advances in the specialty in obstetrics and gynecology are scheduled to be presented at the XX Peruvian Congress of Obstetrics and Gynecology to be held from September 30 to October 3, 2014 The Congress Organizing Committee, chaired by Dr. Alfredo Celis has designated a section of Free Subjects in which has set out the best research and clinical cases selected by a panel of academic leaders of the Peruvian Society of Obstetrics and Gynecology and specialty Committee whose abstracts appear in this Supplement Peruvian Journal of Gynecology and Obstetrics. They have been selected for oral presentation 5 original work gynecology, infertility 4 10 7 obstetrics and fetal and neonatal medicine. There will be special awards for the two best works and one special for the work presented by a resident physician. A novelty in the publication of summaries is that, by the Committee of Free Themes agreement and the sponsorship of the Congress Organizing Committee, this time this section is published as Supplement Peruvian Journal of Gynecology and Obstetrics, similarly to what it is customary in American and European scientific societies that reach the scientific community as a special supplement their institutional magazines. This will allow a wider dissemination of summaries - which are also published in English in the virtual world and can encourage our fellow members and researchers to present new scientific work in the next Congress.